Analysis of Volatile Constituents of Baimaohou (Camellia sinensis L.) by Gas Chromatography-Mass Spectrum - Zhuang, Wuyoung; Cai, Jibao; Su, Qingde (Asian Journal of Chemistry, 2016)
Volatile oil of Baimaohou (Camellia sinensis L.) was obtained by simultaneous distillation-solvent extraction. Following, the essential oil was analyzed by gas chromatography-mass spectrum. 48 components at least were identified, constituting approximately 74% of the oil. The main constituents of the essential oil were phytol (16.4%) and 5,6,7,7a-tetrahydro-4,4,7a-trimethyl-2-(4H)-benzofuranone (10.6%), a very expensive flavour material.